Optimization of AlN/GaN strained-layer superlattice for GaN epitaxy on Si(111) substrate / Yusnizam Yusuf - Yusnizam, Yusuf (2017)
Most works involving GaN technology on Si (111) substrate, especially for device applications suffer from high density dislocations and cracks in the sample which reduces the performance of the devices. The objective of this study is to introduce aluminium nitride/gallium nitride (AlN/GaN) strained-layer superlattice (SLS) structure to avoid abrupt changes in thermal expansion coefficient between epilayer and Si substrate. In addition, this structure reduces the propagation of threading dislocation inside the sample. Indirectly, the structure will reduce the bowing effect on the sample. The growth was performed by introducing nitridation surface treatment (NST) just before depositing high temperature AlN nucleation layer at 1000 °C for different nitridation time of 40,220 and 400 s. Subsequently, AlN/GaN SLS layer of 11 and 13 nm respective thickness with different number of pairs of 20, 40, 60 and 80 pair was grown on top of the AlN nucleation layer. Undoped GaN with thickness of 500 nm was eventually grown on the SLS structure at temperature of 1125 °C to investigate the sustainability of AlN/GaN SLS to avoid cracks on the sample. Although bowing results from X-ray rocking curve (XRC) analysis display optimum, lowest full width half maximum (FWHM) for 60 SLS pairs which suggest a reduction in dislocation with an increase in number of SLS pair. Cross section images of field effect scanning electron microscopy (FESEM) shows fine and abrupt SLS pair structure while surface analysis shows smoother surface with increment in number of SLS pair. Roughness analysis conducted using atomic force microscopy (AFM) correlates well with both XRC results and FESEM surface results. Investigation of bowing effects also provides positive results in which there is an optimum bowing parameters which is required to produce crack-free GaN on Si (111). In conclusion, 60 pairs of AlN/GaN strained-layer superlattice can successfully sustain 1 μm undoped GaN, thus, producing crack-free GaN layer on Si (111) substrate.